2002
DOI: 10.1124/dmd.30.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Metabolism ofp,p′-DDT ando,p′-DDT by Rat Liver Cytochrome P450

Abstract: This paper is available online at http://dmd.aspetjournals.org ABSTRACT:The in vitro metabolism of p,p-DDT [1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane], an important environmental pollutant, was examined in rat liver, focusing on reductive dechlorination. When p,p-DDT was incubated with liver microsomes of rats in the presence of NADPH or NADH, a dechlorinated metabolite, p,p-DDD [1,1-dichloro-2,2-bis(4-chlorophenyl)ethane], was formed under anaerobic conditions together with a dehydrochlorinated metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 36 publications
3
56
0
3
Order By: Relevance
“…The docked conformations were sorted in ascending order with respect to the total energy (the sum of van der Waals as well as electrostatic energy terms of the potential energy function and the ligand's internal energy). The binding modes with the lowest total energies and known hydroxylation sites [trichloromethyl group in DDT (20,37); carbons 4-7 in carbaryl (38); furan ring in xanthotoxin (39)] closest to the heme were chosen for the second round of energy minimization during which all side chains were allowed to move freely.…”
Section: Docking Of Prospective Substrates Into the Cyp6z1 And Cyp6z2mentioning
confidence: 99%
“…The docked conformations were sorted in ascending order with respect to the total energy (the sum of van der Waals as well as electrostatic energy terms of the potential energy function and the ligand's internal energy). The binding modes with the lowest total energies and known hydroxylation sites [trichloromethyl group in DDT (20,37); carbons 4-7 in carbaryl (38); furan ring in xanthotoxin (39)] closest to the heme were chosen for the second round of energy minimization during which all side chains were allowed to move freely.…”
Section: Docking Of Prospective Substrates Into the Cyp6z1 And Cyp6z2mentioning
confidence: 99%
“…5(a)), indicating CYP5013C2 participates in the metabolism of DDT in Tetrahymena. P450 of rat liver is involved in the reductive dechlorination of DDT to DDD, but not to DDE (Kitamura et al, 2002). Our results showed that there were no significant differences in concentrations of DDE among strains of p450-KD, WT, and p450-OE (Fig.…”
Section: Cyp5013c2 Is Involved In the Degradation Of Ddt To Dddmentioning
confidence: 39%
“…Previous studies established that, in rat, most production of DDD is catalyzed enzymatically by the cytochrome P450 through reductive dechlorination of DDT (Kitamura et al, 2002). We therefore sought to test whether this Tetrahymena P450 functioned similarly in the metabolism of DDT.…”
Section: Ddt and Its Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Walaupun termasuk senyawa persisten, DDT di lingkungan dihadapkan berbagai proses yang menyebabkan perubahan-perubahan strukturnya dan membentuk DDD dan DDE, serta pada tingkatan tertentu membentuk DDMU dan DDA (Quensen III et al, 1998;Kitamura et al, 2002). Kondisi lingkungan redoks diakui sebagai faktor penentu perubahan-perubahan DDT menjadi metabolitnya.…”
Section: Ddtunclassified